A Descriptive Study Of 39 Malaysian Web Sites - Abdul Rahman, Dr Mohamed Rafick Khan (2000)
The aim of this study is to evaluate the characteristics of Malaysian organizations web sites based on the type of media used, the response time of opening a web site and their e-mail queries response time.